ANALISIS HUKUM PERKAWINAN KHUNŚA PERSPEKTIF TAFSIR KONTEMPORER - Karaz Rafiqa Diaz; Abdul Muhaimin Zen (CV. Adiba Aisha Amira, 2023)
Humans are created in pairs, male and female to getting marry and having the children. However, there have been cases of ambiguous genetalia referred to khunśa in Islam. Khunśa had two genitals, or none at all, which made her legal marital status ambiguous. On the other hand, there is the phenomenon of sex reassignment surgery and same-sex marriage along with the gender equality issues and LGBT campaigns in public spaces. On that basis, this thesis aims to explain the interpretation of khunśa marriage after sex reassignment surgery according to the perspective of contemporary interpretation and its relevance to the issue of gender equality promoted by LGBT. The author uses library research methods with a qualitative and descriptive analysis approach. The research sources are primary sources obtained from the books of Tafsir al-Jami' li Ahkam Al-Qur'an and Tafsir al-Munir. While secondary sources come from fiqh books, laws, journals, theses, and data from the internet. The result of this study is if khunśa able to fulfill the requirements and pillars of marriage, one of it is clarity of identity or gender, then nothing prevents him from marriage. As for khunśa musykil, whose gender is still in doubt, not allowed to marry, to prevent the same-sex marriage as happened during the time of the companion of Prophet Muhamad ﷺ. Thus causing the breakup of marriage (faskhu nikah). Khunśa is not the same as ‘waria’ or ‘wadam’ or ‘transgender’. In addition to the amount of damage that will occur later, LGBT behavior is a deviation from fitrah that given from Allah